Ozone-Induced Biochemical and Molecular Changes in Vitis vinifera Leaves and Responses to Botrytis cinerea Infections - Margherita Modesti; Alessandra Marchica; Claudia Pisuttu; Samuele Risoli; Elisa Pellegrini; Andrea Bellincontro; Fabio Mencarelli; Pietro Tonutti; Cristina Nali (MDPI AG, 2023)
To investigate how plants cope with multi-stress conditions, we analyzed the biochemical and molecular changes of Vitis vinifera leaves subjected to single or sequential double stresses (infection by Botrytis cinerea (Bc) and ozone (O3, 100 ppb for 3 h) treatment). In Bc+/O3− leaves, the hydrogen peroxide (H2O2) induction (observed at 12 and 24 h from the end of treatment (FET)) triggered a production of ethylene (Et; +35% compared with Bc−/O3− leaves), which was preceded by an increase of salicylic acid (SA; +45%). This result confirms a crosstalk between SA- and Et-related signaling pathways in lesion spread. The ozone induced an early synthesis of Et followed by jasmonic acid (JA) and SA production (about 2-fold higher), where Et and SA signaling triggered reactive oxygen species production by establishing a feedback loop, and JA attenuated this cycle by reducing Et biosynthesis. In Bc+ + O3+ leaves, Et peaked at 6 and 12 h FET, before SA confirmed a crosstalk between Et- and SA-related signaling pathways in lesion propagation. In O3+ + Bc+ leaves, the H2O2 induction triggered an accumulation of JA and Et, demonstrating a synergistic action in the regulation of defence reactions. The divergence in these profiles suggests a rather complex network of events in the transcriptional regulation of genes involved in the systemic acquired resistance.